American Ballet Theatre Now - New York Gala Dance with the Stars - Jaffe, Susan; Carreño, Jose Manuel; MacKerrow, Amanda; Gardner, John (Arthaus, 2001)
The American Ballet Theatre is one of the world's leading ballet companies, and since its foundation in 1940 it has guested at all of the major dance festivals throughout the world. Each year it undertakes an extended tour of the United States of America, reaching a total audience of more than 600,000. It is furthermore one of the few American cultural institutions to be funded by subsidies from the State Department of the United States. To date the American Ballet Theatre has completed fifteen world tours taking it to forty-one different countries. Highly experienced solo dancer Kevin McKenzie took over the leadership of the famous American company in 1992, and it is under his directorship that the American Ballet Theatre will be celebrating its sixtieth anniversary with a series of gala performances in the year 2000. This festive presentation took place in television studio conditions before an invited audience in the New York City Center. During the ninety-minute gala, the leading soloists of the American Ballet Theatre displayed highlights from the company's diverse repertoire. [www.naxos.com]